Performance of a novel fluorogenic chimeric analog for the detection of third-generation cephalosporin resistant bacteria - Park, Mi Jung; Park, Yeon-Joon; Oh, Eun-Jee; Chang, Jiyoung; Kim, Youngsic; Yu, Jinkyung; Park, Kang Gyun; Ahn, Dae-Ro (ELSEVIER SCIENCE BV, 2016)
Resistance to third generation cephalosporins is widely disseminated in Enterobacteriaceae mainly due to extended-spectrum-beta-lactamases, plasmid AmpC beta-lactamases, and hyperproduction of chromosomal AmpC beta-lactamases. Here we evaluated the performance of a novel fluorogenic probe rapid test and compared the results with the phenol red assay using a total of 77 characterized organisms (44 extended-spectrum-beta-lactamases, 33 chromosomal or plasmid AmpC(3-lactamases) and 46 susceptible organisms. The fluorescent assay showed higher sensitivity than the phenol red assay in cefotaximase type extended-spectrum-beta-lactamases, non-cefotaximase type extended-spectrum-beta-lactamases, chromosomal AmpC beta-lactamases, and plasmid AmpC plactamases (96.7% vs. 90.0%, p = 0.157; 71.4% vs. 7.1%, p = 0.003; 100.0% vs. 64.7%, p < 0.001; 100.0% vs. 6.3%, p < 0.001). The fluorescent assay had a positive correlation with the exponents of cefotaxime and ceftazidime minimum inhibitory concentrations (p < 0.001 for both). The new fluorescent assay will be very useful for the rapid detection of resistance to third generation cephalosporins that originates from various beta-lactamases. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: LACTAMASE-PRODUCING ENTEROBACTERIACEAE; BETA-LACTAMASES; RAPID DETECTION; IMPACT